Economic Effectiveness of Straw Pellets Production (Agricultural Engineering, 2017)
The objective of the paper was to present straw pellets production technology and to determine their production costs. The paper presents also the cost structure and economic effectiveness of pellets production. Tests were carried out in EKO-BIOMASA company which produces pellets. It is located in Biechów in Świętokrzyskie Voivodeship. Unit costs of pellets production were: 310.20 PLN ∙ t-1 for option 1, 285.40 PLN ∙ t-1 for option 2 and 278.90 PLN ∙ t-1 for option 3. The most favourable was option 3 when the pellet production was carried out on the technology line in the 3-shift system day and night. In all three variants of pellet production, the highest costs were in case of electric energy. Its participation in the cost structure in relation to the option was within 42% (option 3) and 38% (option 1). The obtained indicator of economic effectiveness for all the investigated options was higher than one.